Industry Structure and Productivity Growth: Panel Data Evidence for Germany from 19712000 - Thomas Fuchs (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2005)
The paper presents a detailed industry-level productivity analysis (52 industries) for the effects of industry structure on TFP growth for Germany from 1971 until 2000. The analysis builds on a theory by Acemoglu et al. (2003) relating industry structure and productivity growth of an industry. The analysis reveals positive effects of vertically disintegrated industries with respect to TFP growth during a convergence period. After the convergence period, there remains only a positive effect for industries which use a higher share of imported intermediate inputs, especially in manufacturing industries, providing evidence for beneficial effects of higher levels of international cooperation on TFP growth. The database of the analysis is the recently collected productivity database for Germany. The Ifo Productivity Database, which is unique due to its high data quality, offers industry- and asset-specific capital data and also for the first time data on domestic and international intermediates input over such a long period. The database allows to allocate productivity growth according to the gross output growth accounting method following Jorgenson and Stiroh (2000).
Keywords: F15; L60; L80; O11; O14; 330; Growth accounting; productivity; sectoral analysis; internationalization; globalization; international outsourcing; panel data